PRINCIPAL LEADERSHIP, WORK DISCIPLINE, AND TEACHER PERFORMANCE: EVIDENCE FROM SMK BUNGA PERSADA, CIANJUR - Lutpi Nurhabibah; Nur Alia Sumanti; Winda Dwi Yanthi (PT. Berkah Digital Teknologi, 2025)
Purpose: This study aims to determine the extent of the influence of the principal's leadership and teacher work discipline on teacher performance at schools in Indonesia, based on the national education objectives outlined in the Preamble to the 1945 Constitution of the Republic of Indonesia, which emphasizes educating the nation’s life and improving public welfare. Research Methodology: The research employs a quantitative approach using questionnaire-based data collection. Data analysis was conducted using SPSS 25 for Windows, involving validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple linear regression analysis. Hypothesis testing was performed using t-tests for partial effects, an F-test for simultaneous effects, and the coefficient of determination (R²) to measure the model’s explanatory power. Results: The results indicate that both the principal's leadership and work discipline have a positive and significant effect on teacher performance. The t-test results show that leadership (t-value = 5.577 > t-table = 2.002; p = 0.000 < 0.05) and work discipline (t-value = 3.381 > t-table = 2.002; p = 0.001 < 0.05) significantly influence teacher performance. Furthermore, the F-test confirms that both variables collectively have a significant effect (F-value = 55.101 > F-table = 3.16; p = 0.000 < 0.05), with a high coefficient of determination indicating a strong model fit. Limitations: The study is limited to a specific geographical area and relies on self-reported data through questionnaires, which may be subject to response bias. Additionally, external factors such as school facilities, student background, and government policies were not included in the analysis. Contribution: This research contributes to educational management by providing empirical evidence that strong leadership and high work discipline are critical drivers of teacher performance. The findings support policy development in school leadership and human resource management, promoting more effective and accountable educational practices in line with national education goals.